MICROCONTROLLER SEBAGAI PENGENDALI WAKTU PENYIRAMAN PADA TANAMAN BUAH-BUAHAN SISTEM TABULAPOT - Watiningsih, Tri; Nursuwening, Yohana; AM, Reni Sulistiyowati (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Availability of land plants is the reason why they do not want to plant crops, especially fruits such as guava, kedondong and others, as academics eager to implement and introduce tabulapot plants that need hygienic fruits can be realized. Along with the question, it is necessary for the introduction of increased community participation in meeting the needs of their own fruits the land more hygienic through Research Lecturer Restoration